What Are the Primary Cues Used by Mammalian Predators to Locate Freshwater Turtle Nests? A Critical Review of the Evidence - Geller, Gregory A.; Parker, Scott L. (Frontiers in Ecology and Evolution, 2022)
ABSTRACT. – Turtle biologists have long been interested in the biotic and abiotic factors that influence the detection of freshwater turtle nests by mammalian predators. Increased knowledge of nest predation dynamics may help develop of conservation strategies to increase turtle nesting success by altering or reducing the signal strength of predominant nest location cues. However, despite this long-standing interest, much of the related research has produced conflicting and sometimes inconsistent results across studies. Here we review much of the existing literature on freshwater turtle nest predation by mammalian predators and attempt to synthesize some general, underlying themes. Available data suggest that raccoons (Procyon lotor) primarily use olfactory cues associated with nest cavity construction, while other predators, including red foxes (Vulpes vulpes) and other canids may use both scents from nesting turtles and their eggs as well as visual nest location cues to locate nests. Changes in rainfall regimes due to anthropogenic climate change may increase turtle nesting success in some areas and decrease it in others via effects on the signal strengths of nest location cues. This review has revealed a strong North American bias in published work, highlighting the need for additional studies of turtle nest predation dynamics in other areas of the world where chelonians are often imperiled elements of the biota.